Cryptosporidium infection and associated factors among diarrheic children under five years of age in Eastern Ethiopia. - Degu Abate; Rea Tschopp; Berhanu Seyoum; Yadeta Dessie; Mahlet Osman Hasen; Gizachew Gemechu; Øystein Haarklau Johansen; David Carmena; Lucy J Robertson; Kurt Hanevik; Alemseged Abdissa (PLoS Neglected Tropical Diseases)
Background Cryptosporidium infection causes diarrhea that may lead to malnutrition, growth faltering, cognitive impairment, and mortality if left untreated. Cryptosporidiosis continues to be a significant public health issue in low-income countries, including Ethiopia. However, its epidemiology among children under five years of age remains understudied. Therefore, this study aimed to determine the prevalence and factors associated with Cryptosporidium infection among diarrheic children under five in Eastern Ethiopia. A cross-sectional study was conducted among children under five years of age attending health centers with diarrhea in Eastern Ethiopia between November 2022 and October 2023. Fecal specimens were analyzed by auramine-phenol staining using light-emitting diode fluorescence microscopy. A structured questionnaire was used to obtain information on sociodemographic and other variables potentially associated with Cryptosporidium infection. Poisson regression with a robust variance model was employed to assess factors associated with Cryptosporidium infection using the prevalence ratio with 95% confidence intervals (CI). Results This study included 756 diarrheic children under five years of age (mean = 20.8 months with a standard deviation of 13.4 and median of 16 months). The prevalence of Cryptosporidium infection was 15.2% (95% CI: 12.7-17.9). Wet season (adjusted prevalence ratio (APR) = 1.7, 95% CI: 1.2-2.4), having caregivers with no formal education (APR = 2.6, 95% CI: 1.1-6.3), presence of a diarrheic member in the household (APR = 1.9, 95% CI: 1.2-3.2), not being exclusively breastfed (APR = 1.6, 95% CI: 1.1-2.3), lack of handwashing practice after toileting (APR = 2.8, 95% CI: 1.7-4.5), and the use of toilet paper after defecation (APR = 1.6, 95% CI: 1.6-3.3) were factors significantly associated with increased risk of Cryptosporidium infection. Conclusions Cryptosporidiosis was highly prevalent in diarrheic children under five years of age in Eastern Ethiopia. Exclusive breastfeeding, improving sanitation, and ensuring proper hygiene practices are essential steps in reducing the risk of Cryptosporidium infection.